Non-linear finite element modelling of reinforced concrete beam / Ismail Abd Rahman - Abd Rahman, Ismail (1997)
In recent years, reinforced concrete has been used with increasing sophistication in the construction of complex structures, such as multi story tall buildings, long span bridges, LRT track and dam. These structures are subjected to a variety of environmental loads, wind, wave forces and do not forget earthquake motions. Under extreme conditions, a structure may be deformed well beyond its linearly elastic range, and hence a nonlinear analysis becomes necessary. In this study, the linear and non linear finite element analysis have been used to modelled the reinforced beam which we can find the suitabie model to represent by comparing the non linear and linear result. For linear analysis, a model with varying E-value for concrete in tension were adopted with two different type of element. The result form non linear analysis will compared with the linear model varying E-value and existing experimental result. Finally, we can conclude of the adtanges of designing non linear analysis instead of linear analysis